Les genres décrits n°2 - Julie Abbou (Glad!)
This chronicle offers a journey through gender in traditional grammars. Different examples are chosen to depict in a playful manner how the gender imaginary is circulated by grammars. These examples draw the landscape of grammatical gender and allow us to playfully outline the imaginary of gender circulated by grammars.